Pemberdayaan Ibu-ibu PKK Kecamatan Babakan Madang Bogor untuk Meningkatkan Kesehatan Kulit Keluarga dan Masyarakat melalui Pemahaman Penyakit Kulit - S, Hadi Firmansyah (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Skin health is an important aspect of public health that is often neglected, especially in the household environment. Low public knowledge about skin diseases can trigger the spread of infection, delays in treatment, and decreased quality of life. This community service aims to increase the knowledge and awareness of PKK mothers in Babakan Madang District, Bogor, about skin diseases through interactive educational activities. The methods used include counseling, practical simulations, group discussions, and pre- and post-test evaluations. The results of the activity showed a significant increase in participants' knowledge about types of skin diseases, symptoms, transmission methods, and prevention. This program has succeeded in empowering PKK mothers as agents of change who can transmit skin health information to families and the surrounding community. This activity is recommended to be continued periodically as part of promotive and preventive efforts at the community level.